Mengurai Potensi Media Sosial dalam Memperkuat Implementasi Kebijakan Keterbukaan Informasi Publik - Suhendra Suhendra; Bambang Suprianto; Faila Sufa Marhamah (Jurnal Media Administrasi, 2024)
This research aims to explore the potential of social media in supporting the implementation of public information disclosure policies. This study employs a qualitative approach with a case study method. Data is collected through in-depth interviews with relevant stakeholders, participant observation, and social media content analysis. The collected data is analyzed using thematic analysis techniques to identify patterns, themes, and insights relevant to the research objectives. Results This research reveals that social media has significant potential in strengthening the implementation of public information disclosure policies. Social media can facilitate wide dissemination of information, enhance public participation, and promote government transparency and accountability. However, challenges such as digital literacy, regulations, and adequate policies must be addressed to fully utilize the potential of social media.